Anesthetic Management Guided by Transthoracic Echocardiography During Cesarean Delivery Complicated by Hypertrophic Cardiomyopathy. Issue 6 (15th March 2016) - DesRoches, Jaclyn M.; McKeen, Dolores Madeline; Warren, Andrew; Allen, Victoria M.; George, Ronald B.; Kells, Catherine; Shukla, Romesh
Abstract : We describe the management of a parturient woman with hypertrophic cardiomyopathy who developed a symptomatic accelerated idioventricular rhythm who required an urgent cesarean delivery at 32 weeks. Transthoracic echocardiography helped guide anesthetic management, including epidural dosing, fluid management, and phenylephrine infusion rates. This case demonstrates the application of transthoracic echocardiography to guide anesthetic management in a parturient woman at risk for cardiovascular compromise.